(untitled) (Medical Forum Monthly, 2020)
Objective: To assess how much the medical students were satisfied with their course work teaching and assessment method and what measures they will suggest for the future to rectify the current situation. It is necessary to determine the quality of the currently applied academic system. Study Design: Cross-Sectional Study Place and Duration of Study: This study was conducted at the Gomal Medical College, Dera Ismail Khan (a public sector medical college) from February to July 2019. Materials and Methods: A random sample of 375 medical students (2nd to final year) was chosen toprovide a structured questionnaire. However, demographic as well as data regarding the objective of the study could be collected only for 357 medical students. SPSS version. 21was used for the analysis of the data using descriptive statistics. Results: There were more 53% (189) females in the studied sample. Most participants (67%) were satisfied with the teaching method and its standard in the college. Twenty-six percent of students expressed the difficulty of interaction among students. Satisfaction with assessment methods was 28%. Satisfaction with lectures using multimedia was up to 72%. There were 50% of students who were not satisfied with self-directed learning. Fifty-seven percent were pleased with the viva examination. There was a sense of academic workload among 29% ofthe students. Twenty six percent students also expressed the need for career counseling. Fifty-six percent of students were satisfied with pre-clinical teaching. Conclusion: There was suggestion of improvingthe lectures and applied training. Moreover, the need for career couselling was pointed out by arranging professional understanding sessions.